p-Hydroxybenzoic Acid and Kaempferol from Desmodium Triquetrum - Elvira Hermawati; Suzanny Dwi Ellita; Lia Dewi Juliawaty; Euis Holisotan Hakim (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2020)
Desmodium triquetrum (Fabaceae) is widely distributed in Indonesia and used as herbal medicines for diuretic, hemorrhoids, tonics, and anti-inflammatory. Two known compounds, p-hydroxybenzoic acid (1) and kaempferol (2), were isolated from the MeOH extract of the leaves of Desmodium triquetrum. The structures of isolated compounds were determined based on 1H and 13C NMR data. The MeOH extract showed very active with 6,5 μg/mL in addition, compound (1) and (2) showed weak cytotoxicity against murine cell leukemia P-388 with IC50 55,0 and 24,7 μg/mL, respectively. Compound (1) was the first reported in this species.Keywords: Desmodium triquetrum, kaempferol, p-hydroxybenzoic acid